2022
DOI: 10.1007/s00520-022-06805-0
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial risk factors for pain and pain-related disability 1 year after surgery for breast cancer

Abstract: Ethics approval: The study was approved by the Ethical Committee of the University Hospitals of Leuven (s60702).Consent to participate: All included patients provided written informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Central sensitization is characterized by an increased excitability of central nociceptive circuits, caused by hypersensitivity to sensory inputs, even in the absence of inflammation or other peripheral noxious stimuli [ 87 ]. High scores on the central sensitization scale were positively correlated with high disability in a Dutch study of patients with chronic spinal pain [ 22 ], other musculoskeletal pain disorders [ 21 , 23 ], or pain-related disability after oncological surgery [ 24 ]. Taken together, women with endometriosis who experience high disability may be at risk for central sensitization and at a higher risk for chronification of their pain; therefore, they may benefit from additional therapeutic options with centrally acting treatments, such as pregabalin or duloxetine [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central sensitization is characterized by an increased excitability of central nociceptive circuits, caused by hypersensitivity to sensory inputs, even in the absence of inflammation or other peripheral noxious stimuli [ 87 ]. High scores on the central sensitization scale were positively correlated with high disability in a Dutch study of patients with chronic spinal pain [ 22 ], other musculoskeletal pain disorders [ 21 , 23 ], or pain-related disability after oncological surgery [ 24 ]. Taken together, women with endometriosis who experience high disability may be at risk for central sensitization and at a higher risk for chronification of their pain; therefore, they may benefit from additional therapeutic options with centrally acting treatments, such as pregabalin or duloxetine [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of their chronic pain, women with endometriosis experience a significant increase in physical and mental disabilities, and a decrease in their quality of life compared with that of normative populations [ 2 , 15 , 16 , 17 , 18 , 19 , 20 ]. Moreover, correlations between central sensitization and pain-induced disability have been reported in various chronic pain conditions, such as chronic spinal pain, musculoskeletal pain, and chronic pain in patients with cancer [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, maladaptive pain cognitions (e.g., pain‐related worrying) or psychosocial functioning (e.g., anxiety and depression) can enhance or facilitate the transmission of nociceptive stimuli to the brain and may contribute to cognitive emotional sensitization of the somatosensory nervous system, with pain facilitation as a possible consequence (Brosschot, 2002; Fregoso et al, 2019; Glare et al, 2019). Several studies have found that postoperative anxiety, depression, and distress are risk factors for persistent pain after breast cancer surgery (Dams et al, 2022; Schreiber et al, 2021). Maladaptive perceptions and thoughts about pain during or after cancer treatment may contribute to the transition from acute to persistent pain in people surgically treated for breast cancer (Oldenmenger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…CS has also received attention as a mechanism for cancer pain because CS could affect pain in about 40% of breast cancer survivors [23,24]. Moreover, CS-related symptoms have the capability to predict the intensity and interference of persistent postsurgical pain 1 year after surgery [25,26]. These findings suggest that the assessment and treatment of CS are important for the appropriate treatment and management of cancer pain.…”
Section: Introductionmentioning
confidence: 99%